The Influence of Digital Financial Literacy, Perceived Usefulness, Perceived Ease of Use, and Perceived Security on Behavioral Intention to Use QRIS among Campus MSMEs - Santi Setriyani; Diena Noviarini; Ringga Sentagi Asa (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the influence of digital financial literacy, perceived usefulness, perceived ease of use, and perceived security on behavioral intention to use the Quick Response Code Indonesian Standard (QRIS) among micro, small, and medium enterprises (MSMEs) operating in a university canteen. A quantitative survey was conducted with 69 respondents selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model met the recommended thresholds for convergent validity, discriminant validity, and reliability. The structural model shows that perceived usefulness (β = 0.308; t = 2.296; p = 0.022) and perceived security (β = 0.320; t = 2.354; p = 0.019) have a positive and significant effect on behavioral intention, whereas digital financial literacy (β = 0.039; t = 0.515; p = 0.607) and perceived ease of use (β = 0.273; t = 1.847; p = 0.065) show no significant effect. The model explains 75.2% of the variance in behavioral intention (R² = 0.752; Q²predict = 0.750). These findings indicate that campus canteen MSMEs are driven to adopt QRIS primarily by perceived benefits and transaction security, rather than by financial literacy or ease of use alone. As an implementation of these findings, a “Kantin Pinter” digital platform prototype was developed, integrating QRIS education, transaction monitoring, ease-of-use, and digital transaction security features.